Struktur Frasa pada Bungkus Makanan Berbahasa Indonesia - S, Ermawati. (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2019)
This article discusses the structure of phrases in Indonesia food wrappers. Phrase structure is a functional arrangement contained in a speech.The food wrapping that was the object of this study was specifically only on Indonesian food wrappers. That is, food warppers that use foreign language are not examined. The main theory used to refer to the phrase structure in this study was the opinion expressed by Sulistyowati (2012) and other opinions. Based on the analysis conducted on food wrappers using Indonesian, it can be concluded that the phrases structure in Indonesian food wrappers found is 1) 1) FN —> N1 + N2 (biskuit kelapa), 2) FN —> N + V (kacang goreng); 3) FN —> N + Adj (sambal hijau), 4) FV —> V + N (serbu durian); 5) FNum —> Num + N (dua kelinci); dan 6) FAdj —> Adj + N (setia kawan). Thus, it can be affirmed that the phrases structure in Indonesian language food wrappers is more dominant to use the FN structure (nominal phrase) than other structures.